2013
DOI: 10.1111/den.12049
|View full text |Cite
|
Sign up to set email alerts
|

Covered self‐expandable metal stent deployment promises safe neoadjuvant chemoradiation therapy in patients with borderline resectable pancreatic head cancer

Abstract: CSEMS should be considered to relieve symptomatic biliary obstruction in patients with BRPHC receiving NACRT in view of the high attainability rate of safe R0 surgery compared to that with PS deployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 23 publications
8
67
1
Order By: Relevance
“…There have been almost no studies of the one drawback associated with the use of MS in PBD procedures: its cost. In their investigation of the cost from the start of PBD until surgery, Kubota et al reported that the use of PS in PBD procedures cost USD 11,545 and that the use of MS cost USD 11,773, indicating no significant difference between the two [ 27 ]. A simulation of individual cases revealed that PS placement with two or more reinterventions was more effective than a single MS placement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been almost no studies of the one drawback associated with the use of MS in PBD procedures: its cost. In their investigation of the cost from the start of PBD until surgery, Kubota et al reported that the use of PS in PBD procedures cost USD 11,545 and that the use of MS cost USD 11,773, indicating no significant difference between the two [ 27 ]. A simulation of individual cases revealed that PS placement with two or more reinterventions was more effective than a single MS placement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation of the cost from the start of PBD until surgery, Kubota et al reported that the use of PS in PBD procedures cost USD 11,545 and that the use of MS cost USD 11,773, indicating no significant difference between the two [ 27 ]. A simulation of individual cases revealed that PS placement with two or more reinterventions was more effective than a single MS placement [ 27 ]. Our study also indicated no significant cost difference associated with the use of different stent types in PBD procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete surgical resection with a pancreaticoduodenectomy (PD) is a required part of a potentially curative multimodality treatment plan for patients with pancreatic head adenocarcinoma . Despite improvements in neoadjuvant and adjuvant therapies, and surgical techniques, only 15% to 20% of patients are candidates for a resection owing to the presence of a distant tumour outside the confines of a resection, or because of locally advanced disease. Select patients with peri‐ampullary cancers require a multi‐organ resection during a PD to achieve margin‐negative resections.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite improvements in neoadjuvant and adjuvant therapies, and surgical techniques, only 15% to 20% of patients are candidates for a resection owing to the presence of a distant tumour outside the confines of a resection, or because of locally advanced disease. [2][3][4][5][6] Select patients with peri-ampullary cancers require a multi-organ resection during a PD to achieve marginnegative resections. [7][8][9][10][11][12] A margin-negative, or R0, resection is critical as better oncological outcomes are associated with a successful R0 resection.…”
Section: Introductionmentioning
confidence: 99%